Case Report: A Novel Ventilated Thermoplastic Mesh Bandage for Post-operative Management of Large Soft Tissue Defects: A Case Series of Three Dogs Treated With Autologous Platelet Concentrates - Berni, Priscilla; Leonardi, Fabio; Conti, Virna; Ramoni, Roberto; Grolli, Stefano; Mattioli, Giovanni (Frontiers in Veterinary Science, 2021)
A ventilated thermoplastic mesh bandage was used for the post-operative management of large soft tissue defects in three dogs. Once the granulation tissue appeared, the wounds were treated with liquid or jellified autologous platelet concentrates, Platelet Rich Plasma (PRP) and Platelet Lysate (PL), to improve the wound healing process. After cleaning the wound with sterile physiological solution, a dressing was performed with several layers of cotton. A window through the layers of cotton was opened above the wound. Then, the platelet concentrate was topically applied, and the bandage was completed by placing, over the access window, a ventilated thermoplastic mesh modelled according to the size and shape of the wound. After 24 hours, it was replaced by a low adhesion bandage. The thermoplastic mesh avoids the direct contact between the wound and the external layers of the bandage, preventing the drainage of the topical agent and the removal of the growing healthy granulation tissue. The bandage proposed in this study is easily applied by the veterinarian and well tolerated by the animal, ensuring high welfare standards in stressed patients presenting compromised clinical conditions.